1997
DOI: 10.1002/(sici)1096-8628(19970613)70:3<324::aid-ajmg20>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of 2q associated with craniosynostosis, ocular coloboma, and limb abnormalities: Cytogenetic and molecular investigation

Abstract: We report on the clinical and cytogenetic findings in a 9-year-old boy with a de novo deletion of 2q, shown by molecular analysis to have arisen from the paternal chromosome. Examination of microsatellite markers indicated deletion of bands 2q24.3 and 2q31. Clinical findings included craniosynostosis, bilateral ocular colobomata, and limb abnormalities, the latter being an emerging association with deletion of this region of 2q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 7 publications
5
26
0
Order By: Relevance
“…Epilepsy was not seen in the patient reported by Nixon et al [1997]. The data reported by Langer et al [2006] thus reinforce our previous hypothesis , that the epileptic phenotype in these patients is specifically associated with the deletion of the genomic area comprised between marker D2S354 (marker d in Fig.…”
supporting
confidence: 87%
“…Epilepsy was not seen in the patient reported by Nixon et al [1997]. The data reported by Langer et al [2006] thus reinforce our previous hypothesis , that the epileptic phenotype in these patients is specifically associated with the deletion of the genomic area comprised between marker D2S354 (marker d in Fig.…”
supporting
confidence: 87%
“…This locus was identified from reports of cytogenetically visible deletions involving 2q31 in patients with syndromal SHFM. Variable limb anomalies, including SHFM, have been described in association with a number of other findings, such as growth delay, developmental disability, microcephaly, cleft palate, craniofacial dysmorphism, seizures, and anomalies of the brain, eyes, heart, and genitalia [Benson et al, 1986;Ramer et al, 1990;Boles et al, 1995;Nixon et al, 1997;Del Campo et al, 1999;Goodman et al, 2002;Pescucci et al, 2007;Svensson et al, 2007;Davidsson et al, 2008;Tsai et al, 2009;Mitter et al, 2010;Dimitrov et al, 2011;Theisen et al, 2011]. The deletions associated with SHFM have varied in size, and most have been sporadic, but some familial cases have been described [Ramer et al, 1990;Del Campo et al, 1999].…”
Section: Balanced/unbalanced Chromosome Rearrangementsmentioning
confidence: 99%
“…Differently sized deletions (5-33 Mb) that partially overlap that of patient 14 and include the HOXD gene cluster have been described in patients with distinct phenotypes except for variable limb abnormalities. [26][27][28][29] The HOXD genes are members of a homeobox gene family encoding highly conserved transcription factors that have an important morphogenetic role in all multicell organisms, mainly by acting on the development of the central nervous system, the axial skeleton, the gastrointestinal and urogenital tracts, and limbs, 30 and they have been suggested as good candidates for causing the limb anomalies in patients with a 2q24q31 deletion. 31 Interestingly, FISH mapping of the distal deletion breakpoint of our patient showed that it lies outside the HOXD gene cluster, but includes HOXD13 and the regulatory elements of the whole cluster (Figure 2b).…”
Section: Discussionmentioning
confidence: 99%